Congenital malformations and assisted reproductive technique: Where is assisted reproductive technique taking us? - Sunita Tandulwadkar; Pooja Lodha; Vineeta Kharb (Wolters Kluwer Medknow Publications, 2012)
Development of ART has great benefit for millions of couples all over the world and with falling fertility rate there are a growing numbers of children born with the help of ART, it is important to investigate potential risks to these children. IVF-ICSI pregnancies are associated with higher risk for multiple gestation, preterm labor and low birth weight. It is an area of great conflict and interest that whether ART is associated with increased congenital malformations or not. So, this article reviews the data and evidences linking ART to congenital malformations.